One-dimensional hybrid nanostructures for heterogeneous photocatalysis and photoelectrocatalysis - Xiao, Fang-Xing (2015)
Semiconductor-based photocatalysis and photoelectrocatalysis have received considerable attention as alternative approaches for solar energy harvesting and storage. The photocatalytic or photoelectrocatalytic performance of a semiconductor is closely related to the design of the semiconductor at the nanoscale. Among various nanostructures, one-dimensional (1D) nanostructured photocatalysts and photoelectrodes have attracted increasing interest owing to their unique optical, structural, and electronic advantages. In this article, a comprehensive review of the current research efforts towards the development of 1D semiconductor nanomaterials for heterogeneous photocatalysis and photoelectrocatalysis is provided and, in particular, a discussion of how to overcome the challenges for achieving full potential of 1D nanostructures is presented. It is anticipated that this review will afford enriched information on the rational exploration of the structural and electronic properties of 1D semiconductor nanostructures for achieving more efficient 1D nanostructure-based photocatalysts and photoelectrodes for high-efficiency solar energy conversion.